2017
DOI: 10.3892/ijmm.2017.2853
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an miRNA-regulated drug-pathway network reveals drug repurposing candidates for myasthenia gravis

Abstract: Myasthenia gravis (MG) is a rare debilitating autoimmune neuromuscular disorder. Many studies have focused on the mechanism and treatment strategies of MG. However, the exact pathogenesis of MG and effective treatment strategies remain unclear. Recent studies have indicated that microRNAs (miRNAs or miRs) can regulate the pathological pathways of MG, suggesting their potential role in novel treatments. In the present study, we created a comprehensive catalog of experimentally confirmed MG risk genes and miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Moreover, exosomal miR-106a-5p expression was shown to be negatively correlated with patient QMGS, indicating its association with MG clinical typing and severity. Interestingly, one of the dysregulated miRNAs by deep-sequencing in the present study, miR-106a-5p has been previously shown to be associated with the pathogenesis of many cancers, including melanoma, colorectal and gastric cancer, MG, [24][25][26] and esophageal squamous-cell carcinoma. [27][28][29][30] Similarly, miR-106a-5p dysregulation has been reported in T-cells of patients with immune diseases, and may inhibit the proliferation, migration, and invasion of carcinoma cells by modulating various mRNA targets.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, exosomal miR-106a-5p expression was shown to be negatively correlated with patient QMGS, indicating its association with MG clinical typing and severity. Interestingly, one of the dysregulated miRNAs by deep-sequencing in the present study, miR-106a-5p has been previously shown to be associated with the pathogenesis of many cancers, including melanoma, colorectal and gastric cancer, MG, [24][25][26] and esophageal squamous-cell carcinoma. [27][28][29][30] Similarly, miR-106a-5p dysregulation has been reported in T-cells of patients with immune diseases, and may inhibit the proliferation, migration, and invasion of carcinoma cells by modulating various mRNA targets.…”
Section: Discussionmentioning
confidence: 63%
“…Human MG risk gene data was acquired using the following two approaches: i) Gene information was obtained by searching certain current databases, including DisGeNET (http://www.disgenet. org/web/DisGeNET/menu) (15) and Online Mendelian Inheritance in Man (http://www.omim.org/) (16); and ii) using the protocols published in our previous studies (6,7), the gene was notably differentially expressed in more than five MG samples using dependable biological laboratorial techniques, and 9,514 items were browsed by manually collecting literature using the terms [myasthenia gravis (MeSH Terms) and English (Language)] and the species 'Homo sapiens' published prior to March 1st, 2017 on the PubMed database (https://www.ncbi. nlm.nih.gov/pubmed); the eligible genes were selected.…”
Section: Methodsmentioning
confidence: 99%
“…nlm.nih.gov/pubmed); the eligible genes were selected. An update was made to the previous catalog of 162 MG risk genes described in our previous study (7) to 245.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the treatment options, immune suppression, thymectomy, intravenous immunoglobulin and plasma exchange are the widely used methods, and prednisolone and azathioprine are commonly administered drugs [9]. The involvement of microRNAs (miRs) in the regulation of the pathological pathways of MG has been previously studied, highlighting their potential role as novel therapeutic pathways [10]. …”
Section: Introductionmentioning
confidence: 99%